SARS‐CoV‐2–related ARDS in a maintenance hemodialysis patient: case report on tailored approach by daily hemodialysis, noninvasive ventilation, tocilizumab, anxiolytics, and point‐of‐care ultrasound. Issue 2 (4th December 2020) - Galassi, Andrea; Casanova, Francesca; Gazzola, Lidia; Rinaldo, Rocco; Ceresa, Marco; Restelli, Elena; Giorgini, Alessia; Birocchi, Simone; Giovenzana, Marco; Zoni, Ulisse; Valli, Federica; Massironi, Laura; et al.
Abstract: Without rescue drugs approved, holistic approach by daily hemodialysis, noninvasive ventilation, anti‐inflammatory medications, fluid assessment by bedside ultrasound, and anxiolytics improved outcomes of a maintenance hemodialysis patient affected by severe COVID‐19. Abstract : Without rescue drugs approved, holistic approach by daily hemodialysis, noninvasive ventilation, anti‐inflammatory medications, fluid assessment by bedside ultrasound, and anxiolytics improved outcomes of a maintenance hemodialysis patient affected by severe COVID‐19.